Two new species of Zhuliangomyces (Amanitaceae) from Hainan Island, China - Huang, Ting; Zhang, Wen-Hao; Huang, Hong-Yan; Gu, Yan-Ming; Tang, Li-Ping (Phytotaxa, 2022)
Two new taxa of Zhuliangomyces, Z. bambusus and Z. terrus, from Hainan Province of China, a tropical region, are proposed based on morphology and molecular systematics. Zhuliangomyces bambusus is characterized by its light brown basidiomata with a grayish tone at age, striate pileus margin, a viscid annulus, predominantly subglobose basidiospores, abundant clamp connections, and habitat in bamboo duff. Zhuliangomyces terrus possesses a chocolate or dark brown pileus when young, brown to pale brown when mature, a non-striate pileus margin, a viscid annulus, predominantly broadly ellipsoid basidiospores, plentiful clamp connections, and it fruits on soil. These two new species are distinctive from related species in the genus Zhuliangomyces, forming two well-supported monophyletic lineages in the phylogenetic tree of the concatenated dataset of ITS-LSU. This is also the first time that the genus is found in tropical China. A key to this genus is also provided.